Evaluating the effectiveness of various forms of physical therapy in low back pain treatment - Weber-Rajek, Magdalena; Lulińska-Kuklik, Ewelina; Orłowska, Klaudia; Czerniachowska, Iwona; Moska, Waldemar (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The incidence of low back pain has led to the search of the most optimal methods of treatment of this condition, including physical therapy. The study focuses on three such methods: peloid therapy, ultrasound therapy, and magnet therapy. Material and Methods. The study sample comprised 70 patients with chronic low back pain resulting from the overload pain syndrome and/or degenerative changes of the joints of the spine. The patients were divided into three groups undergoing three different types of physical therapy: Group I – peat therapy, Group II – ultrasound therapy, and Group III – a wide range of magnet therapy. The VAS scale, Laitinen’s questionnaire, Schober’s test and Oswestry Disability Index were used to assess the effectiveness of the therapeutic methods. Results. In each group of patients, a statistically significant improvement was attained in all tested variables. Comparing the results between treatment groups, a statistically significant difference in the results of the VAS scale was found (with the best results in the group undergoing ultrasound therapy). Posttherapy results of Laitinen’s questionnaire, Schober test and the Oswestry Disability Index revealed no statistically significant differences between the groups. Conclusions. Peloid therapy, ultrasound therapy and magnet therapy used on patients with low back pain, showed analgesic effects, increased patients’ physical activity, and decreased their degree of disability
Keywords: peloid therapy; ultrasound therapy; magnettherapy; low back pain